2012
DOI: 10.1002/hep.25859
|View full text |Cite
|
Sign up to set email alerts
|

Lower liver-related death in African-American women with human immunodeficiency virus/hepatitis C virus coinfection, compared to Caucasian and Hispanic women

Abstract: Among individuals with and without concurrent human immunodeficiency virus (HIV), racial/ethnic differences in the natural history of hepatitis C virus (HCV) have been described. African-Americans have lower spontaneous HCV clearance than Caucasians, yet slower rates of liver fibrosis once chronically infected. It is not clear how these differences in the natural history of hepatitis C affect mortality, in either HIV positive or negative individuals. We conducted a cohort study of HIV/HCV co-infected women fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 26 publications
2
30
0
1
Order By: Relevance
“…Lo Re et al [7] did not find any significant difference in risk of hip fracture between HIV/HCV co-infected and HIV mono-infected patients. Thus, no data were reported in the publication and were not included in the analysis.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Lo Re et al [7] did not find any significant difference in risk of hip fracture between HIV/HCV co-infected and HIV mono-infected patients. Thus, no data were reported in the publication and were not included in the analysis.…”
Section: Resultsmentioning
confidence: 88%
“…HCV co-infection, compared to HIV mono-infected patients, significantly increases the risk of fractures at many sites [7], [28], [29]. Low BMD is a recognized complication of HIV infection [11], HIV/HCV co-infection [30], or use of ART [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increased interest in research related to the development of liver fibrosis in HIV/HCV co-infection in patients of specific racial/ethnic groups, which requires objective methods of assessment [24,25,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that African-American women had a significantly lower mortality rate of liver disease compared to the rates of the other female groups, namely Caucasian and Hispanic. The researchers suggested that the unfavorable course of hepatotropic infections may be due to the ethnic features underlying their progression [25].…”
Section: Introductionmentioning
confidence: 99%
“…(2,4) In contrast, when compared to European-Americans, African-Americans are less likely to progress to cirrhosis. (5,6) While viral or environmental factors may contribute, these marked divergent clinical outcomes in persons of African compared to European descent suggest a role for host genetics.…”
Section: Introductionmentioning
confidence: 99%